Influence of low glycogen storage on blood glucose and blood lactate kinetics during incremental running test - Nakamura, K.; Sengoku, Y.; Ogata, H.; Nabekura, Y. (Japanese Journal of Physical Fitness and Sports Medicine, 2011)
Blood lactate kinetics is an important physiological determinant of endurance exercise performance. Recently, some studies reported that the blood glucose transition point can also be observed (blood glucose threshold; GT) and the GT is consistent with the lactate threshold (LT). However, we have recently reported that blood glucose kinetics and blood lactate kinetics were different during two sets of incremental running tests in the same day. This result suggested that influence of low glycogen storage on GT and LT are different. This study was intended to clarify the effect of low glycogen storage on the blood glucose and the blood lactate kinetics during incremental running test performed two successive days. Eight male endurance runners participated in incremental running test performed two successive days. The main finding was that the blood glucose was significantly lower in the second day than the first day during incremental test, although blood glucose was not different at rest in both days. However, blood lactate was not different form rest to fifth stages in both days, significantly lower only at the final stage in the second day than the first day. Respiratory exchange ration were lower in the second day compared to the first day. GT was significantly higher in the second day than the first day, but LT was not different in both days. We concluded that low glycogen storage effected blood glucose kinetics more than blood lactate kinetics, and resulted in only the change of GT.